Incidence of injuries in Benjamin category in a school of soccer - Rodríguez Sanz, David (Revista Internacional de Ciencias Podológicas, 2008)
Nowadays the practice of sports activities in early ages is very frecuent. This suppose a risk due to the apparition of injuries and the special muscular and osseous development stages, because of all those reasons we should be specially careful with the treatment. In this work I will try to analize the distribution of the injuries that those young players suffer in order to reach a deeper knowledge about this situation which allow us to act reducing theirs frecuency by prevention. The study shows us that a very significant injuries percentage falls on the lower limb with special interes on feet, because of that I strongly recommend the use of multidisciplinar services in order to provide sportsmen with the suitable treatment.
Keywords: Injuries; Statistics; Soccer; Children